2021
DOI: 10.1007/s12155-021-10289-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomass of a Psychrophilic Fungus as a Biocatalyst for Efficient Direct Esterification of Citronellol

Abstract: A biomass-bound lipase from psychrophilic Chrysosporium pannorum A-1 is an efficient biocatalyst for direct esterification of β-citronellol and acetic acid in an organic solvent. The biomass is effectively produced by fungal submerged culture at 20 ℃, which results in lower energy consumption during the production of biocatalyst. Supplementation of the culture medium with calcium carbonate together with olive oil contributed to a significant increase in the active biomass of mycelium in one batch culture and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…, and CaCO 3 5 g L −1 , pH 6) for 4 days at 20 °C on a rotary shaker (150 rpm). 14 After completion of the culture, the mycelium was separated from the post-culture liquid by vacuum filtration and washed with 150 ml of distilled water. The rinsed mycelium was frozen at −20 °C overnight and then lyophilized for 48 hours.…”
Section: Preparation Of the Biocatalyst For Chemoenzymatic Epoxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…, and CaCO 3 5 g L −1 , pH 6) for 4 days at 20 °C on a rotary shaker (150 rpm). 14 After completion of the culture, the mycelium was separated from the post-culture liquid by vacuum filtration and washed with 150 ml of distilled water. The rinsed mycelium was frozen at −20 °C overnight and then lyophilized for 48 hours.…”
Section: Preparation Of the Biocatalyst For Chemoenzymatic Epoxidationmentioning
confidence: 99%
“…In order to improve the cost-effectiveness of the process, enzymes immobilized on carriers are used, which enables their multiple uses. 13,14 An alternative and cheap source of a biocatalyst for chemoenzymatic epoxidation is lipase anchored to the hydrophobic membrane of the mycelium cell wall. To date, mycelium-bound lipase has not been used in chemoenzymatic epoxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the highest reaction conversion was achieved when vinyl ester was used as the acyl donor, with 98% conversion after 96 h. However, the reaction was slow and the reaction time was long. Kutyła et al (2022) investigated the direct esterification of β-citronellol and acetic acid in organic solvents by biomass-bound lipase from the cardiophilic bacterium Chrysosporium pannorum A-1 to prepare citronellyl acetate. A maximum molar conversion value of 98% was obtained in 24 h using a 2:1 alcohol to acid molar ratio and a 3% w/v biocatalyst in hexane at 30 °C.…”
Section: Synthesis Of Citronella Acetate By Lipase Catalyzed Transest...mentioning
confidence: 99%
“…In addition, the other immobilized lipases have been studied for synthesis of citronellyl acetate. Novozyme 435 usually was regarded as a better commercial immobilized lipase in synthesis of citronellyl acetate [10], but the high disturbance rate 600 rpm inevitably consumed a lot of energy and Table 1 Comparing RSP-PFL and RSF-PFL with several lipase-catalyzed reaction systems for synthesis of citronellyl acetate: composition of reaction systems, reaction conditions and reuses a Enzymes studied in this paper b native PFL super to other commercial lipases reported for the synthesis of citronellyl acetate [9] c Candida antarctica lipase B immobilized on acrylic resin [10] d Candida antarctica lipase immobilized on polyvinyl butyral-zirconium alkoxide hybrid hollow tube [8] e a biomass-bond lipase from psychrophilic Chrysosporium pannorum A-1 effectively produced by fungal submerged culture at 20 °C [62] f other compositions g the optimum conversion obtained at the condition different from that in the reuses of biomass-CPL [62] h the stirring condition by magnetic stirrer [62] i no relevant experimental; j relative activity changed from the initial 100% to the percentage value after the nth reuse k the average attenuation rate of relative activity…”
Section: Comparing With Some Lipases For Synthesis Of Citronellyl Acetatementioning
confidence: 99%
“…However, the nonaqueous activity was low for that the conversion was about 32% after 20 h at 30 ℃ and 80 rpm. Also, there was a biomass-bond lipase from psychrophilic Chrysosporium pannorum A-1, which was used to catalyze esterification of citronellol and acetic acid in n-hexane for synthesis of citronellyl acetate [62]. The attenuation rate of relative activity is only 0.19% h −1 , which showed that its stability is expected in the organic reaction phase.…”
Section: Lipasesmentioning
confidence: 99%